Edukasi Pencegahan Stunting dan Pemantauan Tumbuh Kembang Balita sebagai Upaya Mewujudkan Healthy Society for Sustainable Future - Ninik Azizah; Vivin Eka Rahmawati; Dewi Triloka Wulandari (Institut Teknologi dan Bisnis Semarang, 2026)
Stunting remains one of the health issues that impacts the growth, development, and quality of future human resources. Efforts to prevent stunting must be carried out by improving parents’ knowledge of nutritional needs, monitoring growth and development, and early detection of growth disorders in toddlers. This community service activity aims to improve the knowledge of mothers of toddlers regarding stunting prevention through education on the First 1,000 Days of Life (HPK) and monitoring of toddler growth and development. The activity was held on January 15, 2026, at the Sumbermulyo Village Hall, Jogoroto Subdistrict, Jombang Regency, involving 32 mothers of toddlers. The methods used included counseling on stunting prevention, growth and development monitoring, and anthropometric measurements of toddlers, delivered through lectures, discussions, and question-and-answer sessions. An evaluation was conducted using pre- and post-tests to measure participants’ knowledge gains. The results showed that participants enthusiastically engaged in the activity and demonstrated improved understanding of stunting prevention, the importance of growth monitoring, and anthropometric measurements for toddlers. In addition, the anthropometric measurement results provided an overview of the toddlers’ growth status and helped identify children requiring further monitoring. This activity proved effective in increasing the knowledge and awareness of mothers of toddlers regarding stunting prevention efforts and the importance of regular growth and development monitoring. The continuity of educational activities and health monitoring through Posyandu must continue to be supported to improve children’s health and foster a healthy and high-quality generation.